Trans-3, 4-Disubstituted pyrrolidines as inhibitors of the human aspartyl protease renin. Part II: Prime site exploration using an oxygen linker. Issue 8 (15th April 2015) - Sellner, Holger; Cottens, Sylvain; Cumin, Frédéric; Ehrhardt, Claus; Kosaka, Takatoshi; Lorthiois, Edwige; Ostermann, Nils; Webb, Randy L.; Rigel, Dean F.; Wagner, Trixie; Maibaum, Jürgen
Graphical abstract: Abstract: Inhibition of the aspartyl protease renin is considered as an efficient approach for treating hypertension. Lately, we described the discovery of a novel class of direct renin inhibitors which comprised a pyrrolidine scaffold (e.g., 2 ). Based on the X-ray structure of the lead compound2 bound to renin we predicted that optimization of binding interactions to the prime site could offer an opportunity to further expand the scope of this chemotype. Pyrrolidine-based inhibitors were synthesized in which the prime site moieties are linked to the pyrrolidine core through an oxygen atom, resulting in an ether or a carbamate linker subseries. Especially the carbamate derivatives showed a pronounced increase in in vitro potency compared to2 . Here we report the structure–activity relationship of both subclasses and demonstrate blood pressure lowering effects for an advanced prototype in a hypertensive double-transgenic rat model after oral dosing.